Performance native chicken treated by different stocking density and litter type - Rohmadi, Dwi; Harimurti, Sri; Wihandoyo, Wihandoyo (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2021)
This research was aimed to determine the effect of different stocking density and different litter materials on the production performance of native chicken. Material of yhis study was 324-day old chick (DOC) native chickens, reared for 12 weeks. The DOC were randomly devided into 9 treatment groups include a combination of 3 stocking density (8, 12 and 16 bird/m2) and 3 litter materials (rice hulls, wood shavings and corncobs) in 3 replication. A completely randomized factorial design was an applied in the study then followed by Duncan's multiple range tests. The parameters observed were feed consumption (g/bird/12 weeks), body weight gain (g/bird), feed conversion ratio, and mortality (%). The results showed that feed consumption had affected by stocking density (p<0.05), but it had not affected by litter materials type. Feed consumption at densities of 8, 12 and 16 bird/m2 was 3890; 4020 and 4061 g/bird respectively. The highest feed consumption was obtained at a density of 16 bird/m2. Weight gain, feed conversion and mortality had not affected by stocking density and litter material. It can concluded that the body weight gain, feed intake, feed conversion ratio and mortality is same for stocking density 8,12 and 16 bird/m2 an d same for litter type of rice hulls, wood shaving and corncob.